1995
DOI: 10.1021/jo00117a027
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Thermal Cycloreversion of 2,2,6-Trimethyl-4H-1,3-dioxin-4-one and a Related Species: Retro-Diels-Alder Reaction or Concerted Nucleophilic Attack?

Abstract: Calculations up to the MP2/6-31G*//HF/3-21G level have been carried out to study the thermal cycloreversion of 2,2,6-trimethyl-4H-l,3-dioxin-4-one (1) and 2,2,4-trimethyl-6iT-l,3-oxazin-6-one (3). At this level of calculation, the enthalpy of activation for the thermal cycloreversion of dioxinone 1 was found to be 31.3 kcal/mol with zero-point vibrational energy correction. The experimental value for the reaction in solution is 30.4 kcal/mol. The enthalpy of activation for the as of yet unsynthesized oxazinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
(1 reference statement)
0
22
0
Order By: Relevance
“…Thermal decomposition of 1,3-dioxin-4-ones 1 via [4+2] retrocycloaddition, 12 has been well-studied since trapping of intermediate acylketenes 3 with nucleophiles 13 constitutes a synthetically useful acetoacetylation (R 1 = Me), for example in the preparation of β-ketoesters 4 when the trapping nucleophile is an alcohol (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thermal decomposition of 1,3-dioxin-4-ones 1 via [4+2] retrocycloaddition, 12 has been well-studied since trapping of intermediate acylketenes 3 with nucleophiles 13 constitutes a synthetically useful acetoacetylation (R 1 = Me), for example in the preparation of β-ketoesters 4 when the trapping nucleophile is an alcohol (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no computational study on the thermolysis of dialkyl Meldrum's acid to dialkyl ketene has been reported, although thermolysis of different Meldrum's acid derivatives and various dioxinones to acylketenes or cumulenones has been studied. [38][39][40][41] All computations were carried out using Density Functional Theory (DFT) at the B3LYP/6-31G* level of theory. 42 By computing the thermolysis of 5,5 0 -dimethyl Meldrum's acid, an analogue of 5, and using that as a starting point, the energies of the transition structures of a number of derivatives were compared.…”
Section: Lewis Base Activationmentioning
confidence: 99%
“…We reproduced the pseudopericyclic-type transition structures (42) for the extrusion of acetone described by Birney 26 and Kurth and co-workers. 33 However, we could only find one (very flat) transition structure related to the pseudoaxial pyranone products 5 or 29 (calculations were carried out on the methyl pyranosides whereas the synthetic chemistry uses the n-butyl congeners), for the vinyl ether addition; all attempts to find the transition structure corresponding to the pseudoequatorial products failed.…”
Section: Electronic Structure Calculationsmentioning
confidence: 98%